Critical Review on the Future of Teaching and Learning in the Post-Pandemic World: Top Ten Issues and Top Ten Ideas - Solomon Arulraj David (International Journal of Asian Education, 2022)
This paper explores the top ten issues and ideas for the future of teaching and learning in the post-pandemic world. The study uses the researcher's informed reflection as a method. The informed reflector role allows the researcher to explore realities from multiple dimensions by scanning existing teaching and learning scholarship. The subjective accounting, the lack of external verification of the thinking, overshadows limitations. The researcher devises phenomenological bracketing to reduce the researcher to a reflector. The researcher acknowledges that there could be other critical issues and ideas than those in this study. Nevertheless, the reflections shared in this study may contribute to the existing stock of all other contemplations, discussions, and debates